2010
DOI: 10.1002/anie.200907257
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships through Sequencing (StARTS) Defines Optimal and Suboptimal RNA Motif Targets for Small Molecules

Abstract: Hitting the target: A combined computational and experimental approach defines optimal and suboptimal RNA motifs as targets for small molecules through two‐dimensional combinatorial screening. The method, termed structure–activity relationships through sequencing (StARTS), uses information from the sequences of the RNA motifs selected to bind a ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
90
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 10 publications
0
90
0
Order By: Relevance
“…128 A, each RNA motif has statistically significant features that contribute to binding. The features are identified by comparing the rate of occurrence in selected RNAs compared to the rate of occurrence in the RNA library from which the motif was selected.…”
Section: Figurementioning
confidence: 99%
“…128 A, each RNA motif has statistically significant features that contribute to binding. The features are identified by comparing the rate of occurrence in selected RNAs compared to the rate of occurrence in the RNA library from which the motif was selected.…”
Section: Figurementioning
confidence: 99%
“…Velagapudi et al 123 reported a new method called Inforna for sequence-based design of SMIR to target pre-miRs. Inforna integrated a selection-based strategy (Two-Dimensional Combinatorial Screening; 2DCS), 124 a statistical approach (Structure-Activity Relationship through Sequencing; StARTS), 125,126 and the structural information about the RNA target of interest that identified RNA motifs that positively and negatively contributed to binding. After screening and optimization, they selected three compounds for miR-96 precursor, miR-210 precursor, and miR-182 precursor, respectively.…”
Section: Small Molecule Mirna Therapeutic Agentsmentioning
confidence: 99%
“…7 RNA-PSP compares features in 1 (such as a GC step) to the features in selected motifs. A Z-score (which can be converted to the corresponding two-tailed p -value) is computed, which is a measure of statistical confidence that a feature in a selected motif is truly “privileged” for binding to the small molecule (Fig.…”
mentioning
confidence: 99%
“…Previous studies have shown that RNAs with more statistically significant features that contribute positively to molecular recognition are higher affinity. 7, 8 In fact, affinity scales with the sum of the Z-scores for each statistically significant feature, or Sum Z-score. The range of Sum Z-scores for G Neo B and G Kan A are shown in Fig.…”
mentioning
confidence: 99%